2013
DOI: 10.1080/09654313.2012.722928
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Additionality in the EU Cohesion Policies: An Example of Firm-Level Investment Support

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In reality, however, there may be delays in policy implementation, and these delays may also vary significantly between member states. The absorptive capacity of regions and the funds available for co-financing the ECP are the two most cited reasons for delays in the implementation of the ECP funds (BRANDSMA et al, 2013). The implications of this assumption for the RHOMOLO simulations is that, in reality, the medium-and long-run results would be delayed compared with the results presented above.…”
Section: Limitations and Future Workmentioning
confidence: 90%
“…In reality, however, there may be delays in policy implementation, and these delays may also vary significantly between member states. The absorptive capacity of regions and the funds available for co-financing the ECP are the two most cited reasons for delays in the implementation of the ECP funds (BRANDSMA et al, 2013). The implications of this assumption for the RHOMOLO simulations is that, in reality, the medium-and long-run results would be delayed compared with the results presented above.…”
Section: Limitations and Future Workmentioning
confidence: 90%
“…Other important factors that may affect the actual income distributional effects of subsidies (valid for CDP, RDP and SPS) include various market rigidities, farm behavioural effects and region-specific aspects such as credit market imperfections Brandsma et al, 2013). The exact impact depends on the particularities of these factors and on how they interact with subsidies in particular.…”
Section: Theoretical Hypothesismentioning
confidence: 99%
“…Another effect of subsidies (in competitive markets) could be that subsidies may induce farm behavioural changes which may cancel out (or crowd out) private farm activities. For example, Brandsma et al (2013) have shown that the RDP investment support may fully crowd out (substitute) private investments of farms in competitive markets, implying that farm investment would also be undertaken without the support. In this case, the RDP investment support has no impact on farm productivity but represents a full income transfer to farms.…”
Section: Theoretical Hypothesismentioning
confidence: 99%
“…In the literature, there is considerable variation in the estimated impact of investment subsidies, which, among others, reflects differences in circumstances between countries, regions, sectors and firms, differences in the design of policy and delivery (policy implementation details) and differences in the quality of the data and the analytical methods used in the empirical studies (Brandsma et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%